Simple-Structured OLEDs Incorporating Undoped Phosphorescent Emitters Within Non-Exciplex Forming Interfaces: Towards Ultraslow Efficiency Roll-Off and Low Driving Voltage for Indoor R/G/B Illumination - Xu, Ting; Yi, Ruichen; Zhu, Chunqin; Lin, Mingquan (Frontiers in Chemistry, 2021)
To meet the requirement of indoor R/G/B monochrome illumination a simplified OLEDs structure and fabrication process must occur. Herein, a design philosophy of low efficiency roll-off and simple-structure OLEDs incorporating R/G/B phosphorescent ultrathin non-doped emissive layers (EMLs) within non-exciplex forming interfaces a luminescent system by a direct charge trapping mechanism has been reported, which uses bis(2-methyldibenzo[f,h]-quinoxaline)(acetylacetonate)iridium(III) (MDQ)2Ir(acac), bis(3-phenylpyridin-e)iridium(III) (Ir(ppy)3), and bis(3,5-difluoro-2 -(2-pyridyl)phenyl-(2-carboxypyridyl) iridiumII) (Firpic) as R/G/B luminescent dyes, respectively. Although the recombination zone is narrow in the designed OLEDs, the efficiency roll-off of the designed OLEDs are unexpectedly slow, due to stable charge trapping of the emitters and are refrained from concentration quenching in relatively low current density, but the luminance meets the requirement of indoor lighting. With a low threshold voltage of 2.9/2.9/3.5 V, the designed R/G/B phosphorescent OLEDs show an efficiency roll-off as low as 7.6/3.2/4.3% for indoor luminance from 10 cd/m2 to 1,000 cd/m2, respectively. The perspective of R/G/B luminescent dyes on luminous efficiency, chromaticity coordinate drifts, efficiency roll-off, and direct charge trapping has been thoroughly studied. Therefore, our research may help to further develop ideal indoor lighting using a simplified undoped R/G/B OLEDs structure with simultaneous ultraslow efficiency roll-off, low threshold voltage, simplified fabrication process, low reagent consumption, and cost.